The association between circulating saturated fatty acids and thyroid function: results from the NHANES 2011−2012 - Zhao, Wei; Peng, Xinnan; Liu, Yazhuo; Li, Shen; Li, Xinyu; Gao, Zhengnan; Han, Cheng; Zhu, Zizhao (Frontiers in Endocrinology, 2024)
Methods: To explore potential associations, we conducted an investigation with 579 participants from the National Health and Nutrition Examination Survey (NHANES) 2011-2012. Subgroup analyses and multivariable linear regression models were used to estimate the relationships between eleven distinct SFA concentrations and various thyroid parameters.Results: For 579 adults, subgroup analysis of TSH revealed significant differences in nine specific SFAs and the total SFA levels (all p < 0.05). Furthermore, multivariable linear regression analysis identified positive correlations between certain SFAs and various parameters, including thyroid stimulating hormone (TSH), total triiodothyronine (TT3), free triiodothyronine (FT3), thyroid peroxidase antibodies (TPOAb), thyroglobulin antibodies (TgAb), thyroglobulin (Tg), the ratio of FT3 to free thyroxine (FT4) (FT3/FT4), and the thyrotroph T4 resistance index (TT4RI). Conversely, negative correlations were observed between certain SFAs and total thyroxine (TT4), FT4, the ratio of FT3/TT3, and the thyroid feedback quantile-based index (TFQI) (all p < 0.05).These findings collectively suggest associations between SFAs and thyroid parameters, highlighting the need for future studies to elucidate the underlying mechanisms of these interactions.